The Effect of Fused Deposition Modelling Process Parameters on The Quality Of Abs Product - Wan Suaidi, Sharifah Nur Shahirah; bin Azizul, Muhamad Asri; bin Sulaiman, Syabillah (Journal of Automotive Powertrain and Transportation Technology, 2021)
Fused Deposition Modelling is one of the widely used Additive Manufacturing techniques that are used to create functional end use part of Acrylonitrile Butadiene Styrene (ABS) plastic. The need to ensure that the parts have better dimensional accuracy, surface finish and better mechanical properties thus exist in order to create the good quality of functional end use of fabricated part. The aim of this research is to study the effect of process parameters on the quality of ABS product. In order to achieve the optimum performance of the part, Taguchi method have been implemented. In this project, orthogonal array of L9 (33) was used and 9 pieces of samples were determined for 3 parameters namely: layer thickness, infill density and build orientation with 3 levels each. The sample used in this project is tensile specimen as per ASTM D638 type IV. The specimen was designed using SolidWorks and printed using UP Mini 3D Printer. The specimen was observed for dimensional accuracy, surface roughness and tensile strength. From the finding, it is found that the two most significant control factors for all of the output parameters are object orientation and infill density. Object orientation is the most significant control factor followed by infill density. It affects dimensional accuracy, surface roughness and the tensile strength of the printed specimen test the most compared to the control factor of layer thickness.